PERCEIVED ORGANIZATIONAL SUPPORT PENILAIAN KINERJA DAN INFORMATION TECHNOLOGY CAPABILITY PENGARUHNYA TERHADAP KINERJA KARYAWAN - Ningrum Desy Arisandi; siti Mujanah (STIE Mahardhika, 2023)
The purpose of this study is to analyze Perceived Organizational Support (POS), Performance Assessment and IT Capability affect employee performance. Respondents from this study were all employees, namely as many as 75 people, data collection was carried out through a survey with a questionnaire instrument, and data analysis used was multiple linear regression, while F-test and t-test were used to test the hypothesis. The results of this study indicate that POS, Capability of IT, and performance appraisal partially have a significant effect on employee performance, while the hypothesis test as a simultaneously stated that POS, Capability of IT, and performance appraisal have a significant effect on employee performance. This indicates that to improve employee performance, organizational support, IT skills and performance appraisal of employees in the company are needed.